Assessment of existing reinforced concrete shear wall subjected to the earthquake loading - Ahmad Syakir Zakaria, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017